Barriers to belonging: an ecological and appraisal framework for peer relationships, self-awareness, and confidence in deaf and hard of hearing - Alsayed, Abdulrahman (Frontiers in Psychology, 2025)
This systematic review explores the social and emotional development (SED) of Deaf or Hard of Hearing (DHH) individuals, guided by Ecological Systems Theory and the Appraisal Theory of Emotion. These frameworks highlight how language access, identity, communication methods, and environmental factors influence key areas of SED, including emotional regulation, peer relationships, self-awareness, and confidence. Following PRISMA guidelines, a comprehensive search was conducted across seven databases, yielding 2,380 records. After removing duplicates and applying inclusion and exclusion criteria, 23 empirical studies published between 2010 and 2025 were included in the final review. The studies used quantitative (65.2%), qualitative (26.1%), and mixed-methods (8.7%) designs and represented a range of age groups, communication modalities, and geographic settings. Most focused on children and adolescents, with additional research involving adults and preschool-aged individuals. The findings emphasize the importance of inclusive educational settings, consistent language access (signed or spoken), and culturally affirming support in promoting positive SED outcomes for DHH individuals. This review underscores the need to integrate social–emotional goals into educational and clinical practice and encourages interdisciplinary efforts that recognize both the challenges and strengths shaping the development of DHH individuals.